Factors that influence employee motivation at a glove manufacturing company in Malaysia. - Chan, Yin Key; Er, Boon Hua; Lee, Yu Mun; Lim, Xin; Yap, Jing Fung (2020)
The aim of conducting this research project is to study the factors that influence employee motivation at a glove manufacturing company in Malaysia. The factors that may influence employee motivation included pay and benefits, achievement and recognition, work environment, job security as well as training and development. The researchers focus on the employees who are working in a glove manufacturing company in Selangor, Perak, Negeri Sembilan, Kedah, Kelantan and Johor. In this research, we distribute our questionnaire through Google form and 375 data had been collected from the respondents successfully. The data collected from the respondents are analyzed by using Statistical Package for the Social Sciences (SPSS) Version 25 in the pilot study and also the full study. Pearson Correlation Coefficient Analysis and Multiple Regression Analysis are used to test the significant relationship between the independent variables (pay and benefits, achievement and recognition, work environment, job security as well as training and development) and dependent variable (employee motivation). In conclusion, all the independent variables (pay and benefits, achievement and recognition, work environment, job security as well as training and development) are found to be having a positive significant relationship with the dependent variable (employee motivation). Lastly, a summary of the major findings, implications of the research, limitation of the research, and some recommendations are indicated in this study.